2012
DOI: 10.4021/jmc583w
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Perfringens Sepsis With Massive Intravascular Haemolysis: A Rare Presentation

Abstract: Massive intravascular haemolysis is a rare but well-known complication of Clostridium perfringens sepsis. Presence of fever, intravascular haemolysis, numerous spherocytes in peripheral blood smear and septic shock should raise this clinical suspicion. We describe the case of a 66-year-old male who was admitted in the Emergency Room complaining of abdominal pain, vomiting, fever and dark red urine. No relevant findings in physical examination were found. Laboratory tests revealed massive intravascular haemolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…The main takeaways of our investigation lie in RBC parameters and peripheral blood smear findings which are very consistent with the ones found in the reviewed literature, research, and case studies. As in our case severe hemolytic anemia, the presence of spherocytes, ghost cells, and vacuolated neutrophils with evident left shift and without evidence of schistocytes or parasites in peripheral blood smears are a repeating motif in most of the reviewed cases and should unequivocally raise suspicion of C. perfringens infection ( 3 , 4 , 8 , 16 - 21 ). The possibility of finding gram-positive bacilli in the direct gram stain of a patient’s peripheral blood or even bacilli englobed by neutrophil in a regular Giemsa-stained peripheral blood smear was reported but only vacuolated neutrophils in our study were observed ( 8 , 16 ).…”
Section: Discussionsupporting
confidence: 58%
“…The main takeaways of our investigation lie in RBC parameters and peripheral blood smear findings which are very consistent with the ones found in the reviewed literature, research, and case studies. As in our case severe hemolytic anemia, the presence of spherocytes, ghost cells, and vacuolated neutrophils with evident left shift and without evidence of schistocytes or parasites in peripheral blood smears are a repeating motif in most of the reviewed cases and should unequivocally raise suspicion of C. perfringens infection ( 3 , 4 , 8 , 16 - 21 ). The possibility of finding gram-positive bacilli in the direct gram stain of a patient’s peripheral blood or even bacilli englobed by neutrophil in a regular Giemsa-stained peripheral blood smear was reported but only vacuolated neutrophils in our study were observed ( 8 , 16 ).…”
Section: Discussionsupporting
confidence: 58%
“…Without early detection, source control, and antibiotics administration, the course of C. Perfringens septicemia can be rapidly fatal. 1,3,4 We present a case of an unfortunate 50 years old man who was found to have C. Perfringens septicemia early after he died from massive hemolysis and highlight the importance of early consideration of massive hemolysis as part of the differential diagnosis when faced with a critically ill patient presenting with a remarkably black-colored urine and mild methemoglobinemia.…”
Section: Introductionmentioning
confidence: 98%
“…Clostridium Perfringens (C. Perfringens) is an anaerobic gram-positive bacillus that can be present in the human gastrointestinal and genital tracts. 1 C. Perfringens septicemia most commonly occurs in patients who are immunocompromised. There are 5 biotypes of C. Perfringens, based on the type of toxin that is produced: type A, B, C, D, and E. 2 Alpha toxin, which is produced by all C. Perfringens types, is responsible for gas gangrene and myonecrosis in infected tissues; this toxin also possesses hemolytic activity by functioning as an enzyme that splits lecithin into phosphocholine and diglyceride, leading to the development of spherocytosis and interference with the functional integrity of the red blood cell (RBC) membrane and resulting in anemia, jaundice, and in rare cases, massive hemolysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations